Post-Mucilage Distribution, Daily Growth, Mortality, and Hatch Date Timing of Sand steenbras Lithognathus mormyrus (Linnaeus, 1758) Juveniles in the Sea of Marmara - Buminhan Burkay Selçuk; Oğuzhan Ayaz; Gençtan Erman Uğur; Tekin Demirkıran; Uğur Özekinci; Ahsen Yüksek; Ali İşmen; Uğur Altınağaç; Adnan Ayaz; Alkan Öztekin; Yusuf Şen; İsmail Burak Daban; et al. (Aquatic Sciences and Engineering)
Between 2021-2022, a dense mucilage disaster occurred in the Sea of Marmara in Türkiye. Mucilage mostly covered coastal areas, which juvenile fish use for nurseries, growth, and protection. Due to Sand steenbras having been suggested as an environmental bioindicator species for Mediterranean coastal waters, this study attempts to reveal post-mucilage distribution and potential differences on the timing of hatching, daily age, growth, and mortality as revealed by the otolith microstructure. Individuals were sampled using beach seine nets from 12 equally spaced stations along the Sea of Marmara. Its presence and significant abundance in 10 out of 12 stations showed the Sand steenbras to be a common juvenile species for the Sea of Marmara. Hatching occurs between May-January, with peak hatching occurring in October. When considering that the mucilage had completely disappeared from the environment in August, the first set of hatching months can be seen to coincide with the dense mucilage. Thus, Sand steenbras can be considered as able to reproduce under these environmental conditions. The daily age of the Sand steenbras juveniles ranged between 38-235 days, with a mean of 120.3 ± 1.8 days. The daily growth and mortality rates were also calculated respectively as 0.226 mm/day and 4.11%.